Pengaruh Ekstrak Propolis sebagai Edible Coating terhadap Karakteristik Kimia dan Aktifitas Antioksidan Daging Sapi pada Penyimpanan Suhu Ruang - Andre; A. Apriantini; C. Budiman (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2021)
This aim of this study is to determine the effect of using propolis extract as edible coating for beefon chemical characteristics consisting of moisture content, malondialdehyde value and antioxidantactivity at room temperature storage. This research used randomized design with 4 treatments and 3replications. The treatment applied in this study was immersing the meat in propolis extract with differentconcentrations, that are 0.5%, 1.0%, and 1.5% propolis coating. Coating meat with the addition ofpropolis extract was able to have a significant effect at a concentration of 0.5% on water content and theantioxidant activity of coating meat (P <0.05). The addition of propolis extract at various concentrationscan maintain the quality of beef by reducing rancidity during storage. The increasing concentration ofpropolis extract caused the decreasing of MDA value.